Figure 2. Haplotype networks for cytochrome oxidase c subunit 1. A, Nereimyra aphroditoides. B, Nereimyra punctata. C, Nereimyra woodsholea. Each bar across a in A revision of Nereimyra (Psamathini, Hesionidae, Aciculata, Annelida) - Pleijel, Fredrik; Rouse, Greg W.; Nygren, Arne (Zenodo, 2011)
Figure 2. Haplotype networks for cytochrome oxidase c subunit 1. A, Nereimyra aphroditoides. B, Nereimyra punctata. C, Nereimyra woodsholea. Each bar across a line connecting two specimens denotes one mutation. Numbers correspond to specimens numbers in Table 1, and letters indicate origin (G, Greenland; M, Middle Atlantic Bight; N, Norway; S, Sweden; V, Svalbard). : Published as part of Pleijel, Fredrik, Rouse, Greg W. & Nygren, Arne, 2012, A revision of Nereimyra (Psamathini, Hesionidae, Aciculata, Annelida), pp. 36-51 in Zoological Journal of the Linnean Society 164 (1) on page 41, DOI: 10.1111/j.1096-3642.2011.00756.x, http://zenodo.org/record/4720224